Implementing Digital Game-Based Learning for Qur’anic Arabic Learning Using Serious Game Development Method to Increase Arabic Vocabulary - Roseandree, Billdan Satriana; Jenuri, Jenuri; Nurjaman, Asep Rudi (TIN: Terapan Informatika Nusantara, 2024)
The Qur’an is regarded as the source for communication with Allah, while most of Muslims in the world are non-Arabs and could barely speak Arabic, it is becoming a challenge for Muslims to have a deeper understanding of God’s words and deeper connection with Him. By implementing digital game-based learning as an effort to gain traction among the Islamic world, especially in the digital era of Society 5.0, developing a serious game that specialized in solidifying mufradat (Arabic vocabularies) can retain motivation and interest to keep learning the Qur’an by reducing level of stress and boredom, especially Muslim youth living in an age of liberal, this is found to be a serious challenge for the Islamic community to preserve its purity in daily worship. The research method in use is serious game development method, this method fits the unique aspect of a serious game that is comparably different from pure entertainment game development method such as game development life-cycle. Serious game development model involves educational foundations to be a form of game development that orients educational values whilst retaining the fun and engaging aspect of game. The results of this research shown that Qur’anic Arabic serious game using serious game development method is considered acceptable according to the user acceptance test (UAT) indicated by the ratings of 71.57%, this concludes that users found the game to be effective yet engaging to bolster their daily worship and the method being used is effective in implementing game-based learning compared to the conventional game development life-cylce. This result is reliable as supported by Cronbach’s alpha reliability level shown to be reaching 0.954 or is an excellent level of reliability using the IBM SPSS Statistics 26 software.